Understanding drivers of Demand for Emergency Service Trends in Years 2010–2014 in New South Wales: An initial overview of the DESTINY project. (3rd February 2016) - Dinh, Michael M; Berendsen Russell, Saartje; Bein, Kendall J; Chalkley, Dane; Muscatello, David; Paoloni, Richard; Ivers, Rebecca
Abstract: Objective: This study aims to describe the general characteristics and data definitions used in a population‐based data set of ED presentations in New South Wales (NSW), used to form the basis of future‐trend analyses. Methods: Retrospective analysis of the Emergency Department Data Collection registry, which provided clinical and demographic information of ED presentations across all EDs in NSW between 2010 and 2014. Presenting problems and ED diagnoses were classified using broad clinical categories including injury/musculoskeletal, respiratory, cardiovascular, ear nose and throat, and mental health. Presentations were linked by patient to allow for analysis of representations, and population data were obtained from the Australian Bureau of Statistics. Results: There were 11.8 million presentations that were analysed from 150 EDs (80.6% of all EDs). The rate of ED presentations was highest in those aged 85 years and older and appears to increase across all age groups between 2010 and 2014. The most common ED diagnosis categories were injury/musculoskeletal (27.5%) followed by abdominal/gastrointestinal (12.3%), respiratory (9%) and cardiovascular (8%). Both the Systematised Nomenclature of Medicine Clinical Terms (66%) and the International Classification of Diseases (24%) were used to code ED diagnoses. Conclusions: The elderly population had the highest rate of ED attendances. The use of diverse diagnosis classifications and source information systems may present problems with further analysis. Patterns and characteristics of ED presentations in NSW were broadly consistent with those reported in other states in Australia.